Proposal for the construction of an instrument for pharmaceutical care in oncology (Research, Society and Development, 2022)
Introduction: Cancer is the name given to a set of more than one hundred pathologies, which have as common characteristics the initiation by damage to specific DNA genes and the autonomous and disordered growth of cells that acquire the ability to invade adjacent organs and tissues, leading to disorders functional. Objective: Build a model pharmacotherapeutic follow-up form for cancer patients. Method: This is a descriptive study on the construction of a pharmacotherapeutic follow-up form for oncology services. The form will be built and adapted to be evaluated by experts in the field who will be designated as “Expert Judges”. The intention is for it to be an open instrument, which after completion serves as a basis for creating other forms of pharmaceutical care and helps in daily clinical practice, so the instrument will be registered and made available on access platforms. The instrument will be prepared according to the needs of cancer patient care, within the limits of the pharmacist's competence, with the objective of verifying the patient's needs and ensuring that their drug therapy is appropriate and with safe and effective drugs, in addition to used correctly. Future perspectives: Implementation in cancer therapy services; Product registration on the EduCapes portal and Open doors for new development studies in the field of oncology.